The loss of rapidly labelled ribonucleic acid from isolated HeLa cell nuclei - Watts, J. W. (1969)
1. The loss of nucleic acids and protein from isolated HeLa-cell nuclei was studied. During 4hr. incubation at 37° DNA was conserved, but appreciable amounts of RNA and protein were lost. 2. Two classes of nuclear RNA were distinguished: at least 75% of the RNA was lost from the nuclei relatively slowly through degradation to acid-soluble fragments; the rest of the RNA was lost much more rapidly, not only through degradation to acid-soluble fragments but also through diffusion of RNA out of the nuclei into the incubation medium. 3. The RNA that was preferentially lost was the fraction of nuclear RNA that was rapidly labelled when intact HeLa cells were grown in a medium containing radioactive precursors of RNA. 4. The RNA appearing in the incubation medium was apparently partially degraded and had a sedimentation coefficient of about that of transfer RNA. 5. Both the degradation of RNA and the loss of RNA from the nuclei were sensitive to bivalent cations. Low concentrations of Mg(2+) and Mn(2+) greatly increased the rate of degradation of the rapidly labelled RNA to acid-soluble fragments, and produced a corresponding decrease in the amount of RNA diffusing into the medium. At higher concentrations they suppressed both degradation and diffusion of RNA. The cations Ca(2+), Cu(2+), Zn(2+) and Ni(2+) all progressively inhibited both forms of loss of RNA. 6. Salts of univalent cations produced appreciable effects only at ionic strengths of about 0·2, when degradation to acid-soluble fragments was preferentially inhibited. 7. Both ADP and ATP inhibited loss of RNA at about 30mm. 8. It was concluded that the diffusion of rapidly labelled RNA out of the isolated nuclei was not related to the movement of RNA from nucleus to cytoplasm in vivo, but reflected the ease with which the rapidly labelled RNA detached from the chromatin and the permeability of the membranes of isolated nuclei.